The use of the C4.5 Algorithm for Applications Initial Assessment of Disabilities People the Case Study of the Ministry Social Center Wyata Guna Bandung - Gagas Langgeng Dwi Prastyo; Sardjono Sardjono; Reni Nursyanti (International Journal of Research in Community Services, 2023)
The development of information technology is snowballing, data is processed quickly and practically. Several problems often arise. Social instructors often find it difficult to process the data to determine which social service decisions should be provided. Persons with Disabilities are any person who experiences physical, intellectual, mental, and sensory limitations in the long term in interacting with the environment and may experience obstacles and difficulties in participating fully and effectively with other citizens based on equal rights. The Initial Assessment Form is a decision-making instrument through a process called the Initial Assessment. Later, the need for Social Welfare Services (PPKS) can be known as whether the quality is ready to be educated and included in the residential, community, or family categories. The method in this research is to use the Engineering Research Method. The decision tree model produces an accuracy level of 86.6%, the test data is suitable, and 13.3% is not suitable. In determining the service category and calculating the C4.5 Algorithm, it is better to add the number of datasets so that the accuracy of the value is higher.